An Unusual Pneumoperitoneum in an Extremely Low Birth Weight Preterm Newborn - De Rose, Domenico Umberto; Romano, Valerio; Priolo, Francesca; Zecca, Chiara; Maggio, Luca; Vento, Giovanni; Gallini, Francesca (Acta Biomedica Atenei Parmensis, 2021)
Pneumoperitoneum (PP) is a radiological diagnosis, characterized by the presence of air under the diaphragm, that in 90% of cases results from a perforated viscus while in 10% of cases it is not associated to perforation, the so-called non-surgical or spontaneous PP. Spontaneous PP is rare at any paediatric and neonatal age. In the neonatal population, sporadic cases of spontaneous PP have been described, almost invariably following mechanical ventilation. We presented the case of an extremely low birth weight infant (ELBW) with spontaneous PP secondary to pneumomediastinum who has never underwent mechanical ventilation or cardiopulmonary resuscitation. (www.actabiomedica.it)